Diversity and composition of soil microbial communities in the rhizospheres of late blight-resistant tomatoes after Phytophthora infestans inoculation - Zhou, Xinyan; Liao, Liyuan; Chen, Ken; Yin, Yan; Qiu, Lulu; Li, Xinni; Li, Qingshan; Yang, Shangdong (Frontiers in Plant Science, 2025)
Late blight caused by the oomycete Phytophthora infestans poses a severe threat to global tomato (Solanum lycopersicum L.) production. While genetic resistance forms the cornerstone of disease control, the mechanisms underlying cultivar-specific resistance, particularly their interactions with rhizosphere microbiomes, remain poorly understood. To elucidate the mechanisms of tomato cultivar resistance to late blight and screen out antagonistic microorganisms against P. infestans, we investigated the microbial compositions in the rhizospheres of tomato cultivars with different late blight-resistance levels under both natural and P. infestans-inoculated conditions. Considerable differences in soil microbial diversity and composition of rhizospheres were found between late blight-resistant and -susceptible tomato cultivars. Under natural conditions, the resistant tomato cultivar exhibited higher bacterial diversity and lower fungal diversity than that of the susceptible cultivar. Additionally, after P. infestans inoculation, both the resistant and susceptible cultivars showed enrichment of microorganisms with potential antagonistic effects in the rhizospheres. Among them, bacterial genera, such as Pseudomonas, Azospirillum, and Acidovorax, and fungal genera, including Phoma, Arthrobotrys, Pseudallescheria, and Pseudolabrys, were enriched in the rhizospheres of the late blight-resistant tomato cultivar. In contrast, bacterial genera, including Flavobacterium, Pseudolabrys, and Burkholderia-Caballeronia-Paraburkholderia, and the Trichoderma fungal genus were enriched in the rhizospheres of the late blight-susceptible tomato cultivar. Simultaneously, the enrichment of pathogenic microorganisms, such as Neocosmospora and Plectosphaerella, was also detected in the rhizospheres of the susceptible tomato cultivar. Moreover, no enrichment of pathogenic microorganisms occurred in the late blight-resistant tomato cultivar after P. infestans inoculation. These findings suggest that these traits serve as effective defense mechanisms against pathogen invasion in resistant tomato cultivar. Overall, this study provides a comprehensive analysis of the rhizosphere microbial community structures in late blight-resistant and -susceptible tomato cultivars under natural conditions and their response following pathogen inoculation. Additionally, potential antagonistic microorganisms against late blight were also identified. The findings offer valuable insights for effective late blight management in tomatoes and contribute to the development of sustainable agricultural practices.